1996
DOI: 10.1002/(sici)1096-9063(199601)46:1<37::aid-ps339>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Natural products as pesticides: Two examples of stereoselective synthesis

Abstract: Abstract:The strategy and synthetic efforts leading to efficient stereoselective syntheses of thiangazole, a tris-thiazolinyl-oxazole metabolite isolated from Polyangium spp., and of hydantocidin, a spironucleoside metabolite isolated from Streptomyces hygroscopicus, are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Studies even show that use of Streptomycetes enhances growth of the crop plants [6] . The search for new principles in biocontrol of plant pathogens different from the classical used fungicides, is of world wide concern [7][8][9] . Biological control of plant diseases is slow, gives few quick profits, but can be long lasting, inexpensive and harmless to life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies even show that use of Streptomycetes enhances growth of the crop plants [6] . The search for new principles in biocontrol of plant pathogens different from the classical used fungicides, is of world wide concern [7][8][9] . Biological control of plant diseases is slow, gives few quick profits, but can be long lasting, inexpensive and harmless to life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that microbial metabolites may offer new chemical structures with new modes of action which render them less prone to cross‐resistance with commercial fungicides 3. 4 In addition, many such metabolites are readily degraded, often within a few days, in agricultural systems, thus offering the distinct advantage of reduced residual potential for possible harmful side‐effects on non‐target organisms3 in conjunction with effective disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metabolites are still attractive for fungicide development because of the variability in chemical structures and the chance that a newly discovered antifungal microbial metabolite could have a new mode of action and no cross-resistance to commercial fungicides (Fruh et al, 1996;Porter, 1985;Yarbrough et al, 1993). Also, effective compounds of natural origin are expected to be more advantageous than synthetic pesticides, as they have generally a lower environmental impact and are easily biodegradable.…”
Section: Introductionmentioning
confidence: 99%